Urban fragmentation and its psychological impact: critical analysis of the Bicentennial Project in Tunja, Colombia - Calixto Morales, Rubén Dario (2026)
[Introduction:] Urban fragmentation resulting from Tunja’s Bicentennial Project (Colombia) raises socio-environmental and psychological effects that Latin-American scholarship has only partially addressed. [Objective:] To analyse how this fragmentation affects residents’ psychological health and urban sustainability, while providing a framework that other intermediate Latin-American cities can replicate. [Methodology:] A mixed-methods design was used: 120 stratified surveys and 12 semi-structured interviews with residents and shopkeepers; GIS mapping in QGIS to detect physical barriers and changes in accessibility; and quantitative–qualitative triangulation to validate findings (α = 0.84). [Results:] Seventy-five per cent of participants report negative impacts on daily activities. Geospatial indicators show a 32 % drop in inter-neighborhood connectivity and a 4 m² per-capita shortfall in public-space provision. These conditions correlate with a 28 % rise in perceived insecurity and 62 % overall urban dissatisfaction. [Discussion:] Comparing these findings with spatial-justice theory and case studies from Santiago, Mexico City and Recife reveals that interventions lacking an ecosystemic lens deepen socio-spatial inequality in intermediate Latin-American cities. [Conclusions:] As implemented, the works reinforce fragmentation and generate adverse psychological externalities. Three action lines are proposed: (1) green corridors to restore ecological connectivity and serve as a model for community-based coastal restoration elsewhere in the region; (2) mandatory psycho-environmental indicators in building permits; and (3) participatory governance to redirect future urban projects. These contributions offer a transferable framework for cities facing uncontrolled expansion and environmental degradation.